2017
DOI: 10.18203/2394-6040.ijcmph20171790
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of hypertension among adults aged 25-64 years in a rural area of Thrissur in Kerala

Abstract: Background: Lifestyle changes have fuelled the epidemic of obesity, diabetes, hypertension (HTN), dyslipidemia and cardiovascular diseases. Hypertension is a global public health problem Even though it can be controlled by early diagnosis, lifestyle modifications and adequate treatment; many remain unaware of their hypertension, especially in rural areas where not many studies have been done. The objective of this study was to determine the prevalence and risk factors of hypertension among adults in rural Kera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
5
4
0
Order By: Relevance
“…4,9 The prevalence of hypertension increased with age, consistent with prior reports. 2,8,9,[14][15][16] The higher prevalence noted among males was similar to other reported literature. Study by Mohan et al in "The Chennai urban rural epidemiology study" (CURES) in urban Chennai among 26,001 individuals aged >20 years, the prevalence of hypertension in men was 23.2% as compared to that of women 17.1%.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…4,9 The prevalence of hypertension increased with age, consistent with prior reports. 2,8,9,[14][15][16] The higher prevalence noted among males was similar to other reported literature. Study by Mohan et al in "The Chennai urban rural epidemiology study" (CURES) in urban Chennai among 26,001 individuals aged >20 years, the prevalence of hypertension in men was 23.2% as compared to that of women 17.1%.…”
Section: Discussionsupporting
confidence: 91%
“…This is similar to other reported literature from other parts of Kerala and coastal Karnataka. [8][9][10] The percentage of individuals having hypertension was 36.6% in rural area of Kerala as reported by district level household survey (DLHS) IV in 2012-2013. 11 The prevalence of hypertension in our sample was also higher than that reported from other parts of India.…”
Section: Discussionmentioning
confidence: 99%
“…In our study there was increased prevalence of HTN as age increases which is similar to study done by Chethana KV et al 10 and Simon C et al 11 .…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, it was observed that 52.5% females were hypertensive which is in con- cordance with the earlier studies. Our study showed that females had higher prevalence of HT than males but in some parts of world (Zambia, China, Nepal, India) various scholars found in their studies that the prevalence of HT was higher among males (Siziya et al 2012;Maharajan 2018;Prabakaran et al 2013;Sing et al 2014;Banerjee et al 2016;Simon et al 2017;Paul et al 2017;Singh et al 2017;Thapllyal et al 2018).…”
Section: Discussionmentioning
confidence: 45%
“…In India, Puducherry (Paul et al 2017) has shown the highest prevalence of HT (43.3%). Kerala (Simon et al 2017) has reported the second highest prevalence (42.0%) of HT. Another study conducted in Kolkata by Banerjee et al in 2016 has shown that the prevalence of HT was 42.2%.…”
Section: Discussionmentioning
confidence: 99%